1988
DOI: 10.1007/bf02540699
|View full text |Cite
|
Sign up to set email alerts
|

Application of13C NMR to the identification of surfactants in mixture

Abstract: The possibility of using the 13C NMR technique as a preliminary screening for the analysis of manufactured household products is presented. Spectra for several surfactants and related products in water solution were obtained for reference. The application of 13C NMR to commercial products shows that many surfactants can easily be distinguished from one another and determined from a single spectrum without laborious separative pretreatments.The complete analysis of commercial detergents is becoming more and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thus, understanding Tween 60 chemical composition would help formulators not only in forecasting properties of Tween 60 emulsified products but also in choosing Tween 60 concentrations to achieve desired applications. In the past, although the possibility of using NMR techniques as useful analytical tool in the field of polyoxyethylene-type substances was considered [5][6][7], the NMR exploitation in analyzing structure of polysorbate emulsifiers is still limited quantitatively and qualitatively. For instance, 1 H spectra of Tween 20 only picked up NMR signals arising from the sorbitan skeleton, lauric acid tail and polyoxyethylene protons, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding Tween 60 chemical composition would help formulators not only in forecasting properties of Tween 60 emulsified products but also in choosing Tween 60 concentrations to achieve desired applications. In the past, although the possibility of using NMR techniques as useful analytical tool in the field of polyoxyethylene-type substances was considered [5][6][7], the NMR exploitation in analyzing structure of polysorbate emulsifiers is still limited quantitatively and qualitatively. For instance, 1 H spectra of Tween 20 only picked up NMR signals arising from the sorbitan skeleton, lauric acid tail and polyoxyethylene protons, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are very few reports on the application of NMR for studying commercial detergent formulations. In research dating 30–40 years back, a few references describe the application of 13 C NMR for identification of surfactants (Carminati et al, ; Kalinoski and Jensen, ; Kosugi et al, ), whereas more recent publications seem to focus on diffusion and behavior of surfactants and micelles (Griffith et al, ; Hologne et al, ; McLachlan et al, ; Nicolle et al, ; Soderman et al, ). In addition, Visser et al described the specific analysis of polycarboxylate polymers in detergents using liquid extraction, followed by size‐exclusion chromatography ‐ nuclear magnetic resonance (Visser et al, ), and Fournial et al have reported the NMR‐based characterization of commercial nonionic surfactants (Fournial et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The integration of 1 H NMR spectra gave the average value of the alkyl chain length and polyethoxylated part in the case of non-ionic surfactants. 13 C NMR assignment of anionic, cationic and non-ionic surfactants were proposed by Carminati et al [3] as a preliminary screening for the analysis of manufactured products. Fournial et al [4] proposed a 1 H and 13 C study of This study proposes a new correlation equation between surfactant diffusion coefficients and molecular mass using 2D DOSY 1 H NMR experiment.…”
Section: Introductionmentioning
confidence: 99%